Prevalence of body-focused repetitive behaviors among the general population of Saudi Arabia: a cross-sectional study - Alamer, Safiah A.; Alturaiki, Hassan M.; AlSaad, Ali J.; Mousa, Ali M. Al; Almutairi, Amani A.; Al-Sindi, Zahra S.; Motabagani, Dalal M.; AlShehri, Nouran D.; Alshams, Mariam M. (Frontiers in Psychiatry, 2026)
BackgroundBody-focused repetitive behaviors (BFRBs)—including hair-pulling, skin-picking, and nail-biting—are increasingly recognized as behaviors associated with dermatologic, psychological, and social consequences. However, their prevalence in Middle Eastern populations remains underreported.ObjectiveTo estimate the prevalence of BFRBs in the Saudi population and to describe their demographic distribution and clinical characteristics.MethodsA cross-sectional, community-based survey was conducted between June 2023 and July 2024. A total of 740 adults (aged 18–73 years) completed an online questionnaire incorporating the Habit Questionnaire, a brief five-item self-report screening tool assessing repetitive grooming behaviors, including type, frequency, duration, and impact. Study-defined operational criteria classified behaviors occurring ≥5 times per day for at least four weeks together with functional impairment, injury, or medical attention. Statistical analyses included descriptive summaries, Chi-square tests, and logistic regression.ResultsThe prevalence of BFRB-related behaviors meeting study-defined thresholds was 29.1%. Hair-pulling behavior was reported by 19.1% of participants, skin-picking by 13.4%, and nail-biting by 4.3%. Younger age was strongly associated with these behaviors, with prevalence reaching 47.2% in the 18–20-year group and decreasing to 10.1% in participants older than 50 years (p = 0.001). Most affected individuals described symptoms persisting beyond 12 months and reported complications including interference with daily functioning, injuries, and permanent scarring. Only 5.5% had sought medical care. In multivariable analysis, age remained the strongest predictor across all behavior types; female gender was associated with higher odds of hair-pulling and lower odds of nail-biting, while educational level showed no significant association.ConclusionBFRBs, defined by study-specific behavioral thresholds, are common in Saudi Arabia, particularly among younger adults. Gender differences varied by behavior subtype. Despite chronicity and reported physical consequences, few individuals sought medical care. These findings highlight the need for early recognition, increased public awareness, and integration of BFRB screening into primary and mental health services.